Identification and Localization of Peroxisomal Biogenesis Proteins Indicates the Presence of Peroxisomes in the Cryptophyte Guillardia theta and Other "Chromalveolates". (22nd September 2018) - Mix, Ann-Kathrin; Cenci, Ugo; Heimerl, Thomas; Marter, Pia; Wirkner, Marie-Louise; Moog, Daniel
Abstract: Peroxisomes are single-membrane-bound organelles with a huge metabolic versatility, including the degradation of fatty acids (β-oxidation) and the detoxification of reactive oxygen species as most conserved functions. Although peroxisomes seem to be present in the majority of investigated eukaryotes, where they are responsible for many eclectic and important spatially separated metabolic reactions, knowledge about their existence in the plethora of protists (eukaryotic microorganisms) is scarce. Here, we investigated genomic data of organisms containing complex plastids with red algal ancestry (so-called "chromalveolates") for the presence of genes encoding peroxins—factors specific for the biogenesis, maintenance, and division of peroxisomes in eukaryotic cells. Our focus was on the cryptophyte Guillardia theta, a marine microalga, which possesses two phylogenetically different nuclei of host and endosymbiont origin, respectively, thus being of enormous evolutionary significance. Besides the identification of a complete set of peroxins in G. theta, we heterologously localized selected factors as GFP fusion proteins via confocal and electron microscopy in the model diatom Phaeodactylum tricornutum . Furthermore, we show that peroxins, and thus most likely peroxisomes, are present in haptophytes as well as eustigmatophytes, brown algae, and alveolates including dinoflagellates, chromerids, and noncoccidian apicomplexans. Our results indicate that diatoms are not the only "chromalveolate" group devoid of the PTS2 receptor Pex7, and thus a PTS2-dependent peroxisomal import pathway, which seems to be absent in haptophytes ( Emiliania huxleyi ) as well. Moreover, important aspects of peroxisomal biosynthesis and protein import in "chromalveolates"are highlighted.